SISTEM INFORMASI PEMESANAN DAN PENJADWALAN SRI KADARSIH WEDDING ORGANIZER MENGGUNAKAN METODE AGILE SOFTWARE DEVELOPMENT - Ramadaniah, Dedeh; Romahdoni, Muhammad Reza (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2024)
The advancement of information technology is currently growing very rapidly. Various sectors have taken advantage of this technological advancement, including the wedding organizer business. This is indicated by changes in the management of work, which was previously done manually, now using technology. This research aims to overcome the problems of the semi-manual system used by Sri Kadarsih Wedding Organizer, where customers must come directly to obtain booking information and data is recorded in a book, so that data can be lost or damaged and can cause redundancy of schedule data.  In this study using the agile software development system development method. Using data collection techniques of interviews, observations and literature studies. This system was developed using the PHP (Hypertext Preprocessor) programming language using the SQLyog database. The result of this research is an ordering and scheduling information system that is able to facilitate the ordering process, check the availability of service dates and support the operational efficiency of Sri Kadarsih Wedding Organizer. In conclusion, this booking and scheduling information system makes it easy for customers to place orders and check date availability, and helps Sri Kadarsih Wedding Organizer to schedule orders more efficiently, reduce the risk of errors, and improve the accuracy of managing event schedules.